Penerapan Customer Relationship Management sebagai strategi pemasaran berbasis data di PT.Gragaz Berkah Sejahtera - Junjun Kurnia (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Implementing Customer Relationship Management (CRM) as a data-based marketing strategy has become the main focus for many companies in optimizing relationships with customers. This research explores this through a case study at PT. Gragaz Berkah Sejahtera, a pharmaceutical retail company or pharmacy business that adopts this approach. This research aims to identify how PT. Gragaz Berkah Sejahtera integrates technology and Customer Relationship Management (CRM) theory to improve interactions with customers and how to optimize data-based marketing and sales processes. The research method used is a qualitative descriptive analysis method with the object studied being PT. Gragaz Berkah Sejahtera which involves collecting data, implementing CRM technology, and evaluating its impact on customer loyalty, retention, and increasing sales. While the results of this research highlight the company's success in implementing data-based marketing strategies in an effort to improve marketing and sales, as well as increase customer satisfaction, however these results have not achieved maximum success because there are obstacles in implementing the concept of customer relationship management such as system failures. data-based information technology applications. So that efforts to implement CRM programs are disrupted and have an impact on sales which have not achieved significant growth through this data-based marketing strategy. This research can provide important information and insights for other companies wishing to adopt the same approach in an effort to improve relationships with customers and achieve optimal and sustainable marketing and sales.